Sprint and jump performance are determined by localized BIA - An ecological study in track and field adolescent athletes - Oliveira, N. M., Lázari, E., Matias, C. N., Guerra-Júnior, G., & Gonçalves, E. M. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background Raw data obtained through bioelectrical impedance analysis (BIA) have been applied in different populations to assess body fluids and cell integrity. Assessing raw BIA parameters in specific muscles is an emerging method for evaluating muscle function. We investigated the associations of the BIA-derived variables of resistance (R), reactance (Xc) and phase angle (PhA) measured through whole-body (WB) and muscle-localized (ML) methods with performance in the countermovement jump (CMJ) and 50-meter (m) sprint.